Be Healthy Zige Board Game / Badrul Hisham Hussein ... [et al.] - Hussein, Badrul Hisham; Hj. Nuruddin, Nor Azaruddin Husni; Hussein, Shamsul Iskandar; Hussein, Shahril Adlan; Hussein, Kamarul Hashimy (2021)
During the Covid19 pandemic, Malaysians have to stay in their houses to reduce or prevent getting and spreading of Covid19 with people not staying in the same house. People in some places are not allowed to exercise outside their residences. Many Malaysians have their physical, psychology, mental, emotional, spiritual, and social health affected due to being in their residence for too long following Movement Control Order (MCO). The objectives of the boardgame are to get family members and those living in the same residence to be aware of the importance of health during the Covid 19 pandemic in Malaysia., to remind society to interact and exercise to take care, to maintain, or improve their physical, mental, emotional, spiritual, and social health, and to prevent people from getting sick during Covid19 MCO. Research has found that playing boardgame is able to improve health or prevent sickness from isolation. This board game will enable the teaching and learning of health management during Covid19 MCO to the public can be done in a safe setting, such as at home, school, etc. Basic knowledge sharing of health management will not be limited to normal classrooms by a highly qualified person in health management. This innovation will help to maintain or improve public physical, mental, emotional, spiritual, and social health during MCO.